Empirical Study of The Effect of Career Development on Auditor Performance in Public Sector in Indonesia - Friska, Renny; Pramono, Agus Joko; Susanto, Hendra; Akbar, Bahrullah; Suwarno, Suwarno (Research Horizon, 2023)
One way to obtain competitive human resources is by making employees aware of their potential according to their skills. To make employees aware of their potential, one program that companies can implement is a planned and continuous career development program. The purpose of this study is to determine the influence of career development on auditor performance. The research was conducted using a quantitative approach. A total of 250 respondents of auditors were collected for this study from auditors working at public sector organizations in Indonesia. The sampling technique used was random sampling, and the data analysis technique employed was Structural Equation Modeling (SEM). The results of this study show that career development has a positive effect on motivation, affective commitment, perceived organizational support, and performance. Furthermore, motivation, affective commitment, and perceived organizational support are able to mediate the influence of career development on auditor performance.